Volume fractions calculation of a biphasic system on cylindrical tube using gamma ray and MCNP6 code (Brazilian Journal of Radiation Sciences, 2021)
Be determined which is the volumetric fraction. This paper presents a methodology to calculate volumetric fractions on the stratified flow regime, considering a cylindrical tube. A mathematical model of a measurement system was developed using the MCNP6 code. The mathematical equation was developed to calculate the volume fractions using the pulse height distributions obtained by a radiation detector. The stratified flow regime model considers air-oil, air-gasoline and oil-gasoline biphasic flow, in order to evaluate the performance of the proposed equation in fluid combinations with different densities. A comparative study with equations developed for square-section tubes from literature was performed. The study considered geometry of a source of 137Cs, an acrylic tubing measuring 8.0 cm in diameter and a 1¼ × ¾" NaI(T1) detector placed at a position diametrically opposed to a radiation source to measure the transmitted beam. The dimensions and materials to perform the simulation of the detectors were based on information obtained from the gammagraphy technique and the detector was experimentally validated. The volume fractions of each of the fluids were 0 up to 100% with variations of 25%.